2018
DOI: 10.1002/mabi.201700396
|View full text |Cite
|
Sign up to set email alerts
|

Spherical and Worm‐Like Micelles from Fructose‐Functionalized Polyether Block Copolymers

Abstract: This paper presents the synthesis and characterization of d-fructose modified poly(ethylene glycol) (Fru-PEG) and fructose modified poly(ethylene glycol)-block-poly(ethyl hexyl glycidyl ether) (Fru-PEG-b-PEHG) that are both prepared by initiation with isopropyliden protected fructose, followed by deprotection of the sugar. The block copolymers are self-assembled into micelles, and are subsequently characterized by cryo-TEM and dynamic light scattering. The fluorescent dye Nile red is encapsulated as a model hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…However, one must remember that, in living systems, the glycopolymer may not interact with the lectin alone, but adsorption of other proteins found in the blood may be prevalent. Despite the potentially competing nonspecific adsorption of proteins found in biological systems, glycopolymer were found to display high binding to surface receptors on cells in a biological environment. For example, GLUT5 overexpressing breast cancer cells can distinguish between different sugar-based micelles displaying a high affinity to fructose-coated nanoparticles. , Polymeric micelles with fructose pendants showed high selectivity to breast cancer cells while they display low uptake by healthy cells, , thanks to the overexpression of GLUT5 transporters in breast cancer tissue. , The extracellular asialoglycoprotein receptors (ASGP-R) on liver cancer cell HepG2 are capable of detecting different spatial orientations of galactose on the surface of nanoparticles . Polymers with large amount of galactose were observed to display efficient transfection of hepatocytes, while displaying low uptake by cells with low receptor expression .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one must remember that, in living systems, the glycopolymer may not interact with the lectin alone, but adsorption of other proteins found in the blood may be prevalent. Despite the potentially competing nonspecific adsorption of proteins found in biological systems, glycopolymer were found to display high binding to surface receptors on cells in a biological environment. For example, GLUT5 overexpressing breast cancer cells can distinguish between different sugar-based micelles displaying a high affinity to fructose-coated nanoparticles. , Polymeric micelles with fructose pendants showed high selectivity to breast cancer cells while they display low uptake by healthy cells, , thanks to the overexpression of GLUT5 transporters in breast cancer tissue. , The extracellular asialoglycoprotein receptors (ASGP-R) on liver cancer cell HepG2 are capable of detecting different spatial orientations of galactose on the surface of nanoparticles . Polymers with large amount of galactose were observed to display efficient transfection of hepatocytes, while displaying low uptake by cells with low receptor expression .…”
Section: Introductionmentioning
confidence: 99%
“…The focus in the current glyconanoparticles literature is on the relationship between the type of carbohydrate and the cellular uptake by various cell lines. There is some interest in the effect of the nanoparticle shape, ,,,, but there are limited reports that look at the presentation of the glycopolymer chains on the surface, such as the sugar density and its correlation to cell affinity.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recently, glycopolymer-coated nanoparticles have attracted great interest due to the specific binding between them and carbohydrate receptors located on the cancer cell surface, suggesting that these synthetics are potential to deliver agents into tumor cells in a targeted way [13]. Several studies have addressed that the intake of FCN can be substantially observed in tumor cells but rarely in healthy cells [13,41], which is correlated to the overexpressed GLUT5 found on the surface of tumor cells [42,43]. Of note, nanoparticles that are coated with hydrophilic shell manufactured by long polymer chains with high fructose density have great affinity to tumor cells [14].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, glycopolymer-coated nanoparticles have attracted great interest due to the speci c binding between them and carbohydrate receptors located on the cancer cell surface, suggesting that these synthetics are potential to deliver agents into tumor cells in a targeted way [13]. Several studies have addressed that the intake of FCN can be substantially observed in tumor cells but rarely in healthy cells [13,41], which is correlated to the overexpressed GLUT5 found on the surface of tumor cells [42,43]. Of note, nanoparticles that are coated with hydrophilic shell manufactured by long polymer chains with high fructose density have great a nity to tumor cells [14].…”
Section: Discussionmentioning
confidence: 99%